Problems in the use of information communication technology (ICT) faced by the community Sabah / Tony Paridi Bagang ... [et al.] - Bagang, Tony Paridi; Gregory, Natalie Ann; Mohd Tamring, Budi Anto; Kamu, Assis; Ationg, romzi; Tobi, Bernadette (Universiti Teknologi MARA, Sabah, 2022)
The spread of the Covid-19 pandemic has significantly impacted human life worldwide. The entire global community demands lifestyle changes to adapt to new norms. In Malaysia, the increasing spread of the Covid-19 virus has led the government to implement the Movement Control Order (MCO). As a result, routine activities become limited and controlled. In contrast, applications based on technology, information and communication (ICT) have become the main communication platform, especially in using the internet and online transactions. This article identifies the community's problems in Sabah, specifically on the use of ICT in their daily routines. Using a quantitative approach, data was obtained through a Google form survey, with a sample size of 1,128 involving three main districts: Kota Kinabalu, Sandakan, and Tawau. This article found three main problems faced: infrastructure, costing, and security. These problems are interrelated; therefore, the government is advised to improve the existing and future infrastructure development policies to suit current needs.